Application of bioreactor technology for cell culture-based viral vaccine production: Present status and future prospects - Fang, Zhongbiao; Lyu, Jingting; Li, Jianhua; Li, Chaonan; Zhang, Yuxuan; Guo, Yikai; Wang, Ying; Zhang, Yanjun; Chen, Keda (Frontiers in Bioengineering and Biotechnology, 2022)
Bioreactors are widely used in cell culture-based viral vaccine production, especially during the coronavirus disease 2019 (COVID-19) pandemic. In this context, the development and application of bioreactors can provide more efficient and cost-effective vaccine production to meet the global vaccine demand. The production of viral vaccines is inseparable from the development of upstream biological processes. In particular, exploration at the laboratory-scale is urgently required for further development. Therefore, it is necessary to evaluate the existing upstream biological processes, to enable the selection of pilot-scale conditions for academic and industrial scientists to maximize the yield and quality of vaccine development and production. Reviewing methods for optimizing the upstream process of virus vaccine production, this review discusses the bioreactor concepts, significant parameters and operational strategies related to large-scale amplification of virus. On this basis, a comprehensive analysis and evaluation of the various process optimization methods for the production of various viruses (SARS-CoV-2, Influenza virus, Tropical virus, Enterovirus, Rabies virus) in bioreactors is presented. Meanwhile, the types of viral vaccines are briefly introduced, and the established animal cell lines for vaccine production are described. In addition, it is emphasized that the co-development of bioreactor and computational biology is urgently needed to meet the challenges posed by the differences in upstream production scales between the laboratory and industry.